An Additional Mechanism of Action of Abciximab: Dispersal of Newly Formed Platelet Aggregates - Marciniak, Stanley J., Jr.; Mascelli, Mary A.; Furman, Mark I.; Michelson, Alan D.; Jakubowski, Joseph A.; Jordan, Robert E.; Marchese, Peter J; Frelinger, Andrew L. (Thrombosis and Haemostasis, 2002)
The ability of abciximab to prevent fibrinogen binding to activated platelets indicates it may also promote dissolution of platelet-rich thrombi. The present study examined the capacity of abciximab to reverse platelet aggregation in vitro.Experiments were performed on blood from healthy non-medicated donors. Platelet aggregate formation and disaggregation were monitored turbidimetrically. Platelet-bound fibrinogen was measured by flow cytometry. For disaggregation studies, platelets were first stimulated with either ADP or the 11-mer thrombin receptor activating peptide (TRAP), then varying amounts of abciximab were added at periodic intervals after agonist addition. Platelet disaggregation was detected by comparing the extent of light transmittance at 4 min after addition of either abciximab or saline to PRP. ATP release was simultaneously monitored by chemi-luminescence. When added 1 min after low concentrations of ADP, abciximab rapidly (<1 min) dispersed platelet aggregates in a dose-dependent manner, with complete disaggregation observed with 6.25 µg/mL of the β3 antagonist. In contrast, equivalent concentrations of abciximab did not induce appreciable disaggregation to platelets stimulated with TRAP (10 µM). Platelet counts of samples that had undergone complete disaggregation, as assessed by aggregometry, were equivalent to baseline, indicating dispersal of aggregates to single cells. Concentrations of abciximab that produced complete disaggregation induced partial displacement of platelet-bound fibrinogen (52 ± 8% inhibition of fibrinogen binding at 12.5 µg/ml abciximab). The disaggregation effectiveness of abciximab decreased as the time between ADP and subsequent abciximab addition widened, and as the amount of both dense granule release and agonist stimulation increased. However, pre-treatment of platelets with acetylsalicylic acid (ASA) did not potentiate platelet disaggregation induced by abciximab.These data indicate that abciximab facilitates the dispersal of newly formed platelet aggregates in vitro, by partially displacing fibrinogen from activated GPIIb/IIIa receptors. In vivo, abciximab may destabilize coronary thrombi by preventing aggregate formation and dispersing mural thrombi.
Keywords: GPIIb/IIIa; abciximab; platelet aggregation; disaggregation